Private orthodox general educational institutions: creation, development, problems - V. K. Shapovalov; A. G. Plisyuk; L. V. Khalyapina; L. A. Isaeva; O. E. Sorokina (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the study was to analyze the processes of creation and operation of two private Orthodox educational institutions Non-state educational institution «Holy Assumption Orthodox Gymnasium of the city of Stavropol, Stavropol and Vladikavkaz Diocese of the Orthodox Church» and Private educational institution «Orthodox St. Vladimir Gymnasium» in Stavropol, the implementation of state educational programs, the principles and features of the organization and content of the spiritual and moral development and civil and patriotic education of students, the organization of educational, educational and other activities of leaders, teachers and students of these Orthodox educational institutions of the city of Stavropol. The main materials of all types of educational and upbringing activities of the organizations under study are analyzed: curricula and programs, the ratio of the volumes of compulsory general educational disciplines and programs of subjects of dogmatic content. In-depth interviews were conducted with deputy directors for educational work of the Orthodox general educational institutions in which the study was carried out. The results of the study provide grounds for drawing conclusions about the demand for the creation of private Orthodox educational institutions and the need for support in their development to the level of complete general secondary education. The novelty of the presented work lies in the fact that for the first time the history of creation, activities, ways and results of the development of private Orthodox educational institutions in the city of Stavropol are analyzed, which can contribute to the emergence and implementation of new noble initiatives.